Effect of soil and foliar application of nutrients on growth, root nodules and yield of soybean under Vertisols - Barkha Kumari Verma; Vinod Kumar Yadav; Rajendra Kumar Yadav; Manoj Kumar Sharma; Harphool Meena; Manisha Kumawat (Annals of Agricultural Research, 2025)
A field experiment was conducted at Instructional Farm, College of Agriculture, Ummedganj-Kota (Rajasthan) during kharif season of 2022. The experiment was laid out in randomized block design with three replications. The ten treatments were comprised as T1- control, T2-RDF + 2% urea spray at 35 and 60 DAS, T3-RDF + 2% DAP spray at 35 and 60 DAS, T4-RDF + 2% NPK (18:18:18) spray at 35 and 60 DAS, T5-RDF + 0.5% Zn spray at 35 and 60 DAS, T6-RDF + 0.5% Fe spray at 35 and 60 DAS, T7-RDF + 0.5% Fe and 0.5% Zn spray at 35 and 60 DAS, T8- RDF + 2% NPK (18:18:18) + 0.5% Fe spray at 35 and 60 DAS, T9-RDF + 2% NPK (18:18:18) + 0.5% Zn spray at 35 and 60 DAS and T10- RDF + 2% NPK (18:18:18) + 0.5% Fe and 0.5% Zn spray at 35 and 60 DAS. Results indicated that the application of RDF + 2% NPK (18:18:18) + 0.5% Fe and 0.5% Zn spray at 35 & 60 DAS significantly increased plant height (32 and 55.1 cm) at 45 DAS and at harvest, number of root nodules plant-1 (52.2), dry weight of root nodules (48.07 mg plant-1) and leghemoglobin (2.36 mg g-1) content in root nodules at 45 DAS of soybean over rest of the treatments. Application of RDF + 2% NPK (18:18:18) + 0.5% Fe and 0.5% Zn spray at 35 & 60 DAS significantly increased the chlorophyll content (3.01 and 2.35 mg g-1) and leaf area index (5.32 and 3.41) at 45 and 70 DAS of soybean over rest of the treatments.